Thrombin activatable fibrinolysis inhibitor (TAFI) in blood of patients with colon and breast cancer - Kotschy, Maria; Witkiewicz, Wojciech; Freier, Beata; Dubis, Joanna; Kotschy, Daniel (Contemporary Oncology/Współczesna Onkologia, 2010)
Background : It is believed that TAFI takes part in thrombotic and haemorrhagic events and neoplastic diseases. The aim was to determine the concentration of TAFI in blood of patients with colon and breast cancer compared to healthy persons. In the present literature we have not found any data on this subject. Material and methods : Eighty-four persons were enrolled in this study: 27 patients with colon cancer (15 men and 12 women) aged 38 to 83 (mean 65) years, 37 women with breast cancer aged 36 to 69 (mean 53) years and 20 healthy persons (12 men and 8 women) aged 19 to 56 (mean 41) years. In the citrate plasma of examined persons the concentration of TAFI was determined with Imubind TAFIa/ai Antigen, ELISA from American Diagnostica. Results: In plasma of the control group the TAFI concentration was 59.9 ±11.5 ng/ml. Similar levels were observed in the plasma of patients with colon and breast cancer. No statistically significant differences appeared according to sex and age. The grade of clinical progression and tumour growth according to TNM classification had no influence on TAFI level in plasma of colon and breast cancer. Only an increase of cancer malignancy from G1/G2 caused small but statistically significant changes in plasma TAFI concentration. Conclusion: TAFI concentration in plasma of patients with colon and breast cancer was similar to that in controls and did not depend on sex and age, clinical progression or tumour growth.